APLIKASI BIOSURFAKTAN Bacillus subtilis ATCC 19659 DENGAN MEDIA PRODUKSI LIMBAH TAHU UNTUK ENHACED OIL RECOVERY - Rizqy Fachria (Jurnal Teknologi Lingkungan Lahan Basah, 2021)
Biosurfactant as secondary metabolit produced by Bacillus subtilis. It has the ability to emulsify and reduce the surface tension. Biosurfactants produced by B. subtilis is a lipopeptide. Furthermore, biosurfactant can be utilized in microbial enhanced oil recovery (MEOR). In this research, biosurfactant of B. subtilis ATCC 19 659 were evaluated. The production use Nutrient Broth (NB) and soybean liquid waste. Application of biosurfactant in oil recovery showed that biosurfactant of NB recover 2 mL crude oil and biosurfactant of soybean liquid waste medium recover 3.67 mL.